Prototype development of mobile app for trilingual Islamic banking and finance glossary of terms via iOS and android based devices - Dollah, Nafi@Hanafi; Md Ghalib, Mohd. Feham; Sahrir, Muhammad Sabri; Hassan, Rusni; Zakaria, Abdul Wahab; Omar, Zakaria (International Association of Online Engineering Kirchengasse 10/200 A-1070 WIEN Austria, 2017)
The existing use of mobile technology nowadays can be integrated with various forms of learning materials such as electronic books and digital references in a form of dictionary or encyclopaedia. The expansion of Islamic banking practices through various local financial institutions which received vast attention nowadays by educationists and learners for instance, leads to the need in understanding the terminologies used in the industry. In view of this scenario, the paper shed some light on using a workable model for developing a purposeful mobile Islamic banking terminology glossary application in a more convenient way via mobile devices such as iPhone, iPad or any Android-based smart gadgets. The mobile terminology glossary app was designed by using a developmental research design using via rapid prototype instructional design model. The process begun with a need analysis conducted among 225 respondents in International Islamic University Malaysia (IIUM) It further explored the prototype development and its implementations for mobile accessibility by providing multilingual glossary of Islamic banking and finance terminologies (Malay-Arabic-English). This paper reports the findings design and development prototype based on the need analysis stage, inclusive of mapping users’ device type, Internet accessibility, reasons for owning mobile devices, delivery and user interface, and preferred features to be embedded in the mobile app.